An empirical analysis of capital assets condition ratio in local governments: the case of Florida counties. Issue 2 (29th October 2021) - Wang, Xiaoheng; Chen, Can
Abstract : Purpose: The main purpose of this paper is to examine the political, economic and institutional determinants of capital assets condition ratio in American local governments using government-wide financial statements. Design/methodology/approach: Based on capital assets data from the period of 2011–2016 for the 66 Florida counties as reported on their government-wide financial statements, the authors use a panel two-way fixed effects estimation and a dynamic panel generalized method of moments estimation. Findings: The authors find that social-economic factors, fiscal capacity and democratic voters explain the capital assets condition ratio in Florida county governments. Research limitations/implications: The major findings of this study may only apply to county government in one single state. It may raise the issue of the external validity of our research. It provides policy recommendations for local public officials to maintain and upgrade their capital assets. Originality/value: The study utilizes a new approach of capital assets condition ratio to measure county government investment in capital assets based on the government-wide financial statements.